Synthesis Octyl P-Methoxycinnamate as Sunblock by Transesterification Reaction with the Starting Material Ethyl P- Methoxycinnamate - Suzana Suzana; Nunuk Irawati; Tutuk Budiati (Indonesian Journal of Cancer Chemoprevention, 2011)
Synthesis octyl p-methoxycinnamate substance as sunblock, has been done by transesterification reaction. The starting material of the reaction was ethyl p-methoxycinnamate isolated from Kaempferia galanga L.The transesterification reaction was carried out by reacting  ethyl p-methoxycinnamate with octanol. The product was identified by UV-VIS,Infra Red and Mass Spectroscopy. The result of measurements on erythemic %T at various concentrations demonstrate that octyl p-methoxycinnamate is applicable as a sunblock compound.Keywords: octyl p-methoxycinnamate, transesterification, ethyl p-methoxycinnamate, sunblock